Solvent Extraction and Spectrophotometric Determination of Co(II) with Isovanillin Thiosemicarbazone - Lokhande, R.S.; N. Pawar, Rashmi (Asian Journal of Chemistry, 2010)
A new spectrophotometric method is proposed for the determination of Co(II) at microgram level. Isovanillin thiosemicarbazone reacts with Co(II) at pH 8.4 to form a complex which was extracted in ethyl acetate showing maximum absorption at 440 nm. The molar absorptivity and Sandell's sensitivity were calculated to be 0.135 x 103 L-1 cm-1 and 9.89 x 10-5 μg cm-2, respectively. The stoichiometry of the complex was found to be 1 : 2. The developed method has been applied for the determination of Co(II) in synthetic and real samples.